Answer:
1. The equation represent an exponential decay
2. The rate of the exponential decay is -3×2.5ˣ·㏑(2.5)
Step-by-step explanation:
When a function a(t) = a₀(1 + r)ˣ has exponential growth, the logarithm of x grows with time such that;
log a(t) = log(a₀) + x·log(1 + r)
Hence in the equation -3 ≡ a₀, (1 + r) ≡ 2.5 and y ≡ a(t). Plugging in the values in the above equation for the condition of an exponential growth, we have;
log y = log(-3) + x·log(2.5)
Therefore, since log(-3) is complex, the equation does not represent an exponential growth hence the equation represents an exponential decay.
The rate of the exponential decay is given by the following equation;
![\frac{dy}{dx} =\frac{d(-3(2.5)^x)}{dx} = -\frac{d(3\cdot e^{x\cdot ln(2.5)})}{dx} = -3 \times 2.5^x\times ln(2.5)](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%5Cfrac%7Bd%28-3%282.5%29%5Ex%29%7D%7Bdx%7D%20%3D%20-%5Cfrac%7Bd%283%5Ccdot%20e%5E%7Bx%5Ccdot%20ln%282.5%29%7D%29%7D%7Bdx%7D%20%3D%20-3%20%5Ctimes%202.5%5Ex%5Ctimes%20ln%282.5%29)
Hence the rate of exponential decay is -3×2.5ˣ × ㏑(2.5)